Práticas de leitura por meio do uso de notícias postadas em rede social : uma proposta para o ensino de letramentos multissemióticos - Santos, Danielle Neres dos (2023)
This action-research work is based on reading practices to improve the levels of reading skills of students from stage 8 class B, enrolled at the Monsenhor Carlos Camélio Costa State School. During the course of investigation, it was verified the difficulty of the students in aspects of reading comprehension of multisemiotic texts. Therefore, to contribute to the learning process of the students of that institution and to collaborate with the training of Basic Education teachers, a pedagogical notebook was produced as an educational product based on the genre of news published on a social network. In order to increase reading competence, activities were selected and applied that include reading, analysis and interpretation of news, also due to a gap in the development of reading skills regarding informative texts. In addition, in post-truth times, students are susceptible to sharing false information, , which makes essential a categorical intervention so that they can analyze multisemiotic elements in order to verify the information and avoid consequences arising from the absence of a reading. critical and reflective, so that they can analyze multisemiotic elements in order to verify the information and avoid consequences arising from the absence of a critical and reflective reading. With the application of the educational product, a satisfactory, productive and significant result was obtained, since, with the activities developed, the students were able to perceive reading as a necessary social practice for life. Thus, it is expected this research and the didactic sequence presented here will contribute to possible changes in the educational context, involving language teaching. As theoretical support, this work was based on: Leffa (1996), Marcuschi (2008), Rojo (2012 and 2013), Santaella (2012), Solé (2014), Kress and Van Leuween (2010), Koch and Elias ( 2018), Soares (2009), Fairclough (1998) and Dolz, Noverraz and Schneuwly (2004).